Plasmonic sensing using Babinet's principle - Riley, Joseph Arnold; Horák, Michal; Křápek, Vlastimil; Healy, Noel; Pacheco-Peña, Victor (Nanophotonics (Berlin, Germany), 2023)
Developing methods to sense local variations in properties of nearby materials, such as their refractive index and thickness, are important in numerous fields including chemistry and biomedical applications. Localized surface plasmons (LSPs) excited in plasmonic nanostructures have been demonstrated to be useful in this context due to the spectral location of their associated resonances being sensitive to changes in the environment near the plasmonic structures. This manuscript explores Babinet's principle by exploiting LSP resonances excited in complementary metal-dielectric cylindrical plasmonic structures (plasmonic particle-dimers and aperture-dimers in our case). Both plasmonic structures are evaluated numerically and experimentally using electron energy loss spectroscopy (EELS), providing a full physical understanding of the complementary nature of the excited LSP resonances. These plasmonic structures are then exploited for dielectric sensing under two configurations: when a thin dielectric film is positioned atop the plasmonic structures and when the analyte surrounds/fills the plasmonic particles/apertures. The complementary sensing performance of both proposed structures is also evaluated, showing the approximate validity of the Babinet principle with sensitivity values of up to ∼650 nm/RIU for thin dielectric sensing.
Keywords: plasmonic dimers; Babinet; plasmonics; nanoantennas; dielectric sensing; nanoparticles